Uma estratégia para o gerenciamento da replicação parcial de dados XML - Moreira, Ériko Joaquim Rogério (2009)
XML has become a widely used standard in representing and exchanging data among Web Applications. Consequently, a large amount of data is distributed on the Web and stored in several persistence medias. Relational DBMSs XML-enabled provide concurrency control techniques to manage such data. However, XML data structure makes it difficult implementation of these techniques. Additionally, replication techniques have been used to improve management of large amounts of XML data. Current researches of XML data replication consist of to adapt existing concepts to semi-structured model. In particular, full replication provides a large of locks, due to updates that have occurred on all copies of the base. Moreover, the partial replication aims to increase concurrency among transactions, with a smaller amount of blocks in relation to total replication. This work presents the RepliXP, towards for management of partial replication of XML data. It is presented as a mechanism that combines features of synchronous and asynchronous replication protocols to reduce the amount of update locks. In order to evaluate the strategy, performance tests were carried out by analyzing the response time of transactions. Full and partial replication approaches were compared in RepliXP. According to the results, RepliXP using the strategy of partial XML data replication provided an improvement in response time of concurrent transactions.